An Analysis of the Economic and Social Factors Affecting Real Convergence in Romania - Otilia Georgiana Floroiu (Ovidius University Annals: Economic Sciences Series, 2022)
It is essential that a high level of real convergence is achieved before joining the euro area, as major differences can lead to difficulties in managing the business cycles, in the absence of an independent monetary policy. Therefore, each country should ensure a sufficient level of GDP per capita before the accession. But what can be considered sufficient? Looking back, most euro candidates had a GDP per capita level of 70%-80% of the EU level when adopting the euro currency. Although Romania has made significant progress lately, the following still need to be achieved: labor market reforms, massive infrastructure investments, reducing the regional gaps, increasing innovation investments, and growing budget revenues. The purpose of this paper is to identify the economic and social factors that influence real convergence in Romania, as we believe that working towards increasing real convergence will create the right framework for improving nominal convergence performance.